Attentional Alterations in Alcohol Dependence Are Underpinned by Specific Executive Control Deficits. (20th May 2014) - Maurage, Pierre; de Timary, Philippe; Billieux, Joël; Collignon, Marie; Heeren, Alexandre
<x xml:space="preserve">Abstract</x> Background Attentional biases and deficits play a central role in the development and maintenance of alcohol dependence, but the underlying attentional processes accounting for these deficits have been very little explored. Importantly, the differential alterations across the 3 attentional networks (alerting, orienting, and executive control) remain unclear in this pathology. Methods Thirty recently detoxified alcohol‐dependent individuals and 30 paired controls completed the Attention Network Test, which allow exploring the attentional alterations specifically related to the 3 attentional networks. Results Alcohol‐dependent individuals presented globally delayed reaction times compared to controls. More centrally, they showed a differential deficit across attention networks, with a preserved performance for alerting and orienting networks but impaired executive control (p < 0.001). This deficit was not related to psychopathological comorbidities but was positively correlated with the duration of alcohol‐dependence habits, the number of previous detoxification treatments and the mean alcohol consumption before detoxification. Conclusions These results suggest that attentional alterations in alcohol dependence are centrally due to a specific alteration of executive control. Intervention programs focusing on executive components of attention should be promoted, and these results support the frontal lobe hypothesis.